Collaborative integration or policy diversification: the influence of policy synergy on regional green development - Chang, Yanjun; Wang, Shuai (Frontiers in Environmental Science, 2023)
Enhancing the green and high-quality development of urban in China and exploring the synergistic effects of multiple policy implementations is the key to effectively playing the leading role of policies. To explore the synergistic effects and driving mechanisms of dual policies on regional green development, this study selected panel data from 30 provinces in China from 2008 to 2020.Employing Multi-period difference-in-differences and Mediation effects models, the research systematically explores the synergistic effects of these dual-pilot policies on urban green and highquality development. The findings of this study reveal a significant improvement in the level of urban green development under the influence of the dual-pilot policy. After conducting a series of rigorous tests for robustness, this conclusion remains valid. This improvement is primarily attributed to the stimulation of technological innovation capabilities and the optimization of industrial structures within the cities. Compared to the carbon emissions trading city single pilot and free trade zone city single pilot, the dual pilot effect of carbon emissions trading and free trade zone city is stronger. The carbon emissions trading city pilot and free trade zone city pilot have a synergistic effect on regional green and high-quality development. This research provides valuable theoretical insights to guide the planning of pilot cities, facilitating the realization of both high-quality economic development and sustainability objectives.